Mechanical and dynamic mechanical thermal properties of ensete fiber/woven glass fiber fabric hybrid composites - POLAT, YUSUF (ELSEVIER SCI LTD, 2021)
This study aimed to identify the effects of the stacking sequences on mechanical and dynamic mechanical properties of ensete/glass hybrid composites. The composites were fabricated by using 4 layers of carded ensete web and woven glass fabric by Vacuum-assisted resin transfer molding method. Mechanical and dynamic mechanical properties of hybrid composites were characterized. The test results showed that hybridization of ensete web with glass woven fabrics enhanced the mechanical properties of ensete composites. The morphology of fractured samples reveals that higher glass fibers pullout than ensete fibers in hybrid composites. The flexural properties also increased when glass fiber hybridized with ensete fiber and the optimum values obtained when it is used as the skin of the composite.The composites stacked as glass-ensete-glass (GEEG) showed higher storage modulus as compared to glass-ensete (GGEE) ensete composites whereas loss modulus of the composites reinforced with glass fiber exhibited the maximum value of 407 MPa and the height of the damping curve decreased in GEEG composite. Experimental studies showed that the ensete/glass fiber hybrid polyester composites can be used as load-bearing structures and components where high resistance to deformations and thermal stability is necessary.
Keywords: Ensete fiber; Glass fabrics; Hybrid composites, Mechanical properties; Dynamic mechanical properties; BAMBOO/GLASS FIBER; TENSILE PROPERTIES; WOVEN JUTE; BANANA